2020
DOI: 10.3390/agronomy10081107
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Field Characterization of Teff [Eragrostis tef (Zucc.) Trotter] Variation: From Agronomic to Sensory Traits

Abstract: Teff is an important food crop that serves to prepare Injera-flat-bread. It is cultivated worldwide and is particularly susceptible to lodging. A diverse collection of teff [Eragrostis tef (Zucc.) Trotter] populations was characterized for a wide range of traits, ranging from agronomic to final Injera sensory parameters, under well-irrigated Mediterranean spring conditions. The populations tested were collected from single plants presenting lodging resistance at the site of collection and their traits were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Tef’s morphological characteristics including plant height, lengths of the panicle, the peduncle, the internodes (culm length), thickness of the basal internodes, angle of the panicle, tiller number, root characteristics and the relationship of these plant parts with each other are known to influence the degree of lodging in tef (Bayable et al ., 2020; Blösch et al ., 2020; Girma, 2019; Ketema, 1983; Van Delden et al ., 2010), besides environmental conditions and agronomic practices (Ben‐Zeev et al ., 2020; Merchuk‐Ovnat et al ., 2020). The reduction in culm length and increased thickness of the first and second basal internodes are likely factors for the increased lodging resistance observed for the sd‐1 tef lines.…”
Section: Discussionmentioning
confidence: 99%
“…Tef’s morphological characteristics including plant height, lengths of the panicle, the peduncle, the internodes (culm length), thickness of the basal internodes, angle of the panicle, tiller number, root characteristics and the relationship of these plant parts with each other are known to influence the degree of lodging in tef (Bayable et al ., 2020; Blösch et al ., 2020; Girma, 2019; Ketema, 1983; Van Delden et al ., 2010), besides environmental conditions and agronomic practices (Ben‐Zeev et al ., 2020; Merchuk‐Ovnat et al ., 2020). The reduction in culm length and increased thickness of the first and second basal internodes are likely factors for the increased lodging resistance observed for the sd‐1 tef lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing plant height by inhibiting plant growth regulators or introducing dwarfing genes could lead to crop yield reductions [ 47 ]; hence, researchers have suggested targeting traits other than plant height to reduce yield loss due to lodging. A recent study by Merchuk-Ovnat, et al [ 49 ] suggested that early lodging is likely caused by a rapid increase in inflorescence weight [ 49 ]. This group also observed variations among the tested tef population in terms of lodging time and strength, with some populations possessing the strength to hold the inflorescence in the grain filling season up to a certain point before they were bent to the ground.…”
Section: Mechanisms Of Tolerance To Lodging and Environmental Constraints In Tefmentioning
confidence: 99%